Эффективность внешнеэкономической деятельности предприятия - Рыжко, Е. И.; Жудро, Н. В. (БНТУ, 2021)
Knowledge for work in foreign economic activity should combine basic knowledge of economics, finance and management, as well as a basis for international cooperation. The foreign trade and foreign policy of the state of the country has a dependence, which should include in export and import operations, the norms of international regulation.